Find the derivative of the function. \[ g(x)=\frac{3}{x^{6}}+\frac{2}{x^{2}}+9 \sqrt[3]{x} \] \( g^{\prime}(x)=\square \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To find the derivative \( g'(x) \) of the function \( g(x)=\frac{3}{x^{6}}+\frac{2}{x^{2}}+9 \sqrt[3]{x} \), we can rewrite the function in a simpler form using negative exponents: \[ g(x) = 3x^{-6} + 2x^{-2} + 9x^{\frac{1}{3}}. \] Now, applying the power rule (where the derivative of \( x^n \) is \( n x^{n-1} \)), we differentiate each term: 1. For \( 3x^{-6} \): \[ \frac{d}{dx}(3x^{-6}) = 3 \cdot (-6)x^{-6-1} = -18x^{-7}. \] 2. For \( 2x^{-2} \): \[ \frac{d}{dx}(2x^{-2}) = 2 \cdot (-2)x^{-2-1} = -4x^{-3}. \] 3. For \( 9x^{\frac{1}{3}} \): \[ \frac{d}{dx}(9x^{\frac{1}{3}}) = 9 \cdot \frac{1}{3} x^{\frac{1}{3}-1} = 3x^{-\frac{2}{3}}. \] Now combine these results: \[ g'(x) = -18x^{-7} - 4x^{-3} + 3x^{-\frac{2}{3}}. \] Thus, the derivative is: \[ g'(x) = -\frac{18}{x^7} - \frac{4}{x^3} + \frac{3}{x^{\frac{2}{3}}} \] So finally, \( g^{\prime}(x)= -\frac{18}{x^{7}} - \frac{4}{x^{3}} + \frac{3}{x^{\frac{2}{3}}} \).